Lipid production is more than doubled by manipulating a diacylglycerol acyltransferase in algae. Issue 1 (10th November 2020) - Zhang, Yu; Pan, Yufang; Ding, Wei; Hu, Hanhua; Liu, Jin
Abstract: Oleaginous algae have the ability to synthesize a high level of triacylglycerol (TAG) and are considered as the next‐generation feedstock for biofuel production. Manipulating algal lipid biosynthetic pathways has potential to overproduce TAG and represents a feasible way toward bringing down algae‐derived biofuels production cost. Here we dissected functional roles and engineering potential of six diacylglycerol acyltransferase (DGAT) genes from the marine alga Phaeodactylum tricornutum . PtDGAT1, PtDGAT2B, and PtDGAT3, residing at the chloroplast endoplasmic reticulum (ER) readily for utilizing both chloroplast‐ and ER‐derived diacylglycerol, were transcriptionally correlated with TAG accumulation. Heterologous expression in yeast, in vitro assay and overexpression in P. tricornutum all supported that PtDGAT1 surpassed the other five PtDGAT s in synthesizing TAG. Compared to wild type P. tricornutum, the PtDGAT1 ‐overexpressing strain produced more than doubled TAG and total lipids, which reached 57% and 73% of dry weight, respectively, record‐high levels ever achieved in this alga. Our results demonstrated the strategy of screening proper engineering targets and manipulating a single gene to pull carbon flux to lipids for TAG hyper‐accumulation without growth compromise. The engineered alga with a great trait improvement may serve as a potent lipid producer for production uses. Abstract : Diacylglycerol acyltransferase (DGAT) is considered as a rate‐limiting enzyme of triacylglycerol (TAG) biosynthesis. Here we characterized the roles of six DGAT genes from the marine alga Phaeodactylum tricornutum from multiple aspects: PtDGAT1 surpassed the other five PtDGATs in synthesizing TAG and its overexpression resulted in the accumulation of more than doubled TAG and total lipids, which reached 57% and 73% of dry weight, respectively, record‐high levels ever achieved in this alga. Our results demonstrated the strategy of screening proper engineering targets and manipulating a single gene to pull carbon flux to lipids for algal TAG hyper‐accumulation without growth compromise.